Cav1.2 Activity and Downstream Signaling Pathways in the Hippocampus of an Animal Model of Depression - Rojas-Montecinos, P; Hardy-Traverso, P (NLM (Medline), 2020)
Functional and morphological modifications in the brain caused by major mood disorders involve many brain areas, including the hippocampus, leading to cognitive and mood alterations. Cav1.2 channel expression has been found to increase in animals with depressive-like behaviors. Calcium influx through these channels is associated with changes in excitation-transcriptional coupling by several intracellular signal pathways that are regulated by its C-terminus region. However, which of these signaling pathways is activated during the development of depressive-like behaviors is not known. Here, we evaluate the phosphorylation and expression levels of crucial kinases and transcription factors at the hippocampus of rats after 21 days of chronic restraint stress. Our results show that rats subjected to CRS protocol achieve less body weight, have heavier adrenal glands, and exhibit depression-like behaviors such as anhedonia, behavioral despair and decreased social interaction. Cav1.2 mRNA and protein expression levels, plus l-type calcium current amplitude, are also increased in treated rats when compared with control animals. Out of the three main signaling pathways activated by l-type currents, we only observed an increment of CaM-NFAT axis activity with the concomitant increment in Fas ligand expression. Thus, our results suggest that CRS activates specific pathways, and the increased expression of Cav1.2 could lead to neuronal death in the hippocampus.